2020
DOI: 10.1093/cid/ciaa1156
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Nasopharyngeal Swab and Early Morning Saliva for the Identification of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2)

Abstract: Background The ideal SARs-CoV-2 testing method would be accurate and also be patient-performed to reduce exposure to healthcare workers.  The aim of this study was to compare patient-performed testing based on a morning saliva sample with the current standard testing method, healthcare worker-collected sampling via a nasopharyngeal swab (NPS). Methods This was a prospective single center study which recruited 217 asymptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
164
8
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(194 citation statements)
references
References 18 publications
17
164
8
3
Order By: Relevance
“…It is also reported to have a reduced time and cost [12], and decreased risk of transmission in the community and to HCWs, making it a convenient and safe means of mass testing. There is increasing evidence that the viral load in saliva is comparable or higher than that in the nasopharynx [4,[13][14][15]. We have shown that the CT values were comparable between saliva and NPS, representing a similar viral load in both samples.…”
Section: J O U R N a L P R E -P R O O F Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…It is also reported to have a reduced time and cost [12], and decreased risk of transmission in the community and to HCWs, making it a convenient and safe means of mass testing. There is increasing evidence that the viral load in saliva is comparable or higher than that in the nasopharynx [4,[13][14][15]. We have shown that the CT values were comparable between saliva and NPS, representing a similar viral load in both samples.…”
Section: J O U R N a L P R E -P R O O F Discussionsupporting
confidence: 47%
“…However, the low PPA of 66.7% may limit its suitability to replace NPS as the gold standard diagnostic test. Existing studies have also shown varying PPA or concordance rates, when comparing saliva detection rates to NPS, with reported positive concordance rates ranging from 45.6% [13] to 94.8% [17]. The vast differences in concordance rates may be accounted for by the limitations in sample collection.…”
Section: J O U R N a L P R E -P R O O F Discussionmentioning
confidence: 99%
“…Next, we compared the Ct values between the groups G3 (NOP+/saliva-) and G4 (NOP+/saliva+). It was observed that the Ct values were lower in patients positive in both NOP and saliva samples (median [IQR], 21.5 [19][20][21][22][23][24][25][26][27]) compared to those positive only in NOP samples (29 [25][26][27][28][29][30][31][32][33], P = 0.01, Wilcoxon's rank-sum test) for the E gene. Moreover, these results were also found for the S gene (Figure 2(b)).…”
Section: Rt-pcr Cycle Thresholds In Saliva and Nop Samplesmentioning
confidence: 99%
“…When this study began, saliva was not an accepted specimen type, and procurement of saliva collection devices with stabilizers was limiting. (Table S1) (2)(3)(4)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)). Importantly, the tested population, the saliva collection method, and the processing protocol have varied between the studies, making comparison of results challenging.…”
mentioning
confidence: 99%